The bending and tension strength of furniture joints bonded with polyvinyl acetate nanocomposites - Bardak, Timucin; Naci Tankut, Ali; Tankut, Nurgul; Aydemir, Deniz; Sozen, Eser (Maderas. Ciencia y Tecnología, 2017)
Furniture is the general name given for the portable equipment used in various human activities such as seating, working and relaxing. They can be a product of design and is considered a form of decorative art. They can widely be manufactured with different adhesives. Biodegradable and biobased adhesives which have no toxic compounds and non-dangerous elements have been selected since the furniture is generally benefited in interior locations. Meanwhile, polyvinyl acetate (PVAc) is a thermoplastic polymer which is widely used in the furniture industry. In this study, tension and bending strength of the furniture joints bonded with polyvinyl acetate adhesives filled with nano-TiO2 and nano-SiO2 were investigated. Three materials; oak (Quercus robur) wood, beech (Fagus orientalis) wood and plywood made with beech veneers were selected, and the joints were prepared by mortise and tenon joints. The results showed that the maximum value for the tension strength and bending strength were obtained to beech wood and oak wood in 2% addition of nano-SiO2 fillers. The minimum values for the tension and bending strength nano-SiO2 were found to plywood and 4% loading.